Existence of Solutions for Fractional Differential Equations with p-Laplacian Operator and Integral Boundary Conditions - Jingli Xie; Lijing Duan (Journal of Function Spaces)
In this paper, we investigate a class of integral boundary value problems of fractional differential equations with a p-Laplacian operator. Existence of solutions is obtained by using the fixed point theorem, and an example is given to show the applicability of our main result.